Transformation of the Bessel light beams during it’s propagation in dyes solutions and liquid crystal media - Nazarov, Sergey A.; Gorbach, Dmitriy V.; Tolstik, Aleksey L. (Journal of the Belarusian State University. Physics, 2018)
In this work the results of the experimental investigations of the transformation of contineous, nano- and picosecond pulse duration Bessel light beams during it’s propagation in controlled by external voltage liquid crystall cell and «Rhodamine 6G» dye solution are repesented. Changing of the polarization, phase and spatial structure of the Bessel light beams has been analysed. It is shown, that selfdifraction is observed during the propagation of the pulse laser radiation in the dye solution. This effect leads to the appearance of an additional ring structured distribution of the intensity in the far field of the Bessel light beam. While propagating in the liquid crystall cell, transformation of the linear polarized Bessel light beam of the zero order to the beam with the orthogonal polarization and azimuthally-modulated distribution of the intencity, charasteric for the beam of the second order, has been realized.
Keywords: Bessel light beams; optical vortex; selfdifraction; liquid crystals